Designing Educational and Home Computers in State Socialism: The Polish and Czechoslovak Experience. - Wasiak, Patryk; Švelch, Jaroslav (Journal of Design History, 2023)
This article investigates the design of two comparable microcomputers that were built under state socialism in neighboring countries: Poland (Elwro Junior) and Czechoslovakia (Didaktik Gama). Both computers were "clones" of the highly popular British ZX Spectrum computer. In our article, we discuss the decisions that informed the design of the local "clones" of the British computer, and how both endeavors were supposed to solve specific problems identified by the communities involved in their design. We argue that different configurations of power—in which the actors that took part in the design of both computers were embedded—were the primary reason why these similar products, the ZX Spectrum clones, were "scripted" in a substantially different manner. The Junior was designed as an "educational computer" envisaged as an aid to schooling, while the Gama was a more flexible "home computer." Our investigation focuses on how their designers projected, or "scripted," possible forms of computer use, and who they imagined would be the users of these machines. We also compare both computers with the high-profile One Laptop Per Child project to demonstrate the wider relevance of our study and the usefulness of our investigative toolset to the intersection of design studies and science and technology studies.